Dose recommendations for gentamicin in the real-world obese population with varying body weight and renal (dys)function. (12th August 2020) - Smit, Cornelis; van Schip, Anne M; van Dongen, Eric P A; Brüggemann, Roger J M; Becker, Matthijs L; Knibbe, Catherijne A J
Abstract: Background: The impact of weight on pharmacokinetics of gentamicin was recently elucidated for (morbidly) obese individuals with normal renal function. Objectives: To characterize the pharmacokinetics of gentamicin in real-world obese patients, ultimately to develop dose recommendations applicable across the entire obese population. Methods: In two large Dutch hospitals, all admitted patients with BMI ≥25 kg/m 2 with at least one gentamicin administration, at least one gentamicin and at least one creatinine serum concentration measurement were included. Data from one hospital, obtained from electronic health records, combined with prospective data of non-obese and morbidly obese people with normal renal function, served as the training dataset, and data from the second hospital served as the external validation dataset. Results: In the training dataset [1187 observations from 542 individuals, total body weight (TBW) 52–221 kg and renal function (CKD-EPI) 5.1–141.7 mL/min/1.73 m 2 ], TBW was identified as a covariate on distribution volume, and de-indexed CKD-EPI and ICU stay on clearance (all P  <   0.001). Clearance was 3.53 L/h and decreased by 0.48 L/h with each 10 mL/min reduction in de-indexed CKD-EPI. The results were confirmed in the external validation (321 observations from 208 individuals, TBW 69–180 kg, CKD-EPI 5.3–130.0 mL/min/1.73 m 2 ). Conclusions: Based on the study, we propose specific mg/kg dose reductions with decreasing CKD-EPI values for the obese population, and extension of the dosing interval beyond 24 h when CKD-EPI drops below 50 mL/min/1.73 m 2 . In ICU patients, a 25% dose reduction could be considered. These guidelines can be used to guide safe and effective dosing of gentamicin across the real-world obese population.